BETTY FREUND: A NURSE IN FRANCE PART V - Hugo, Betty (Scientia Militaria - South African Journal of Military Studies, 2012)
BETTY’S LETTERS HOME 3 July 1916 ... You have no idea how awfully cold it was last week, the poor soldiers, what they must suffer, and the war won’t be over this year - Yesterday the South African Ambulance gave a concert in one of the big hotels here. We made 3 000 francs. It is for a poor-hospital we sort of support aswell ... I see the Germans are going as far as Madeira now. I suppose we won’t hear from Africa as much.